HER2 Status in Male Breast Carcinoma: a Single North African Institution Experience of 10 Cases and Review of the Literature - Meriem N Mrabent; Noria Harir; Feriel Sellam; Soumia Zeggai; Abdenacer Tou; Mustapha Diaf; Rachida Salah; Soraya Moulesshoul (Journal of Surgery and Surgical Research - Peertechz Publications, 2015)
Background: To investigate clinic-pathological characteristics, hormonal receptors and HER2 receptor of male breast cancer. Materials and methods: Retrospective study of 10 cases between 2010 and 2013. The studied parameters were: tumor size, histological type, histological grade, lymph node status, hormonal status and overexpression of HER2. Results: The average age of our patients was 60.2 years, in 70% of cases; the histological size that was found was T4; and infiltrating ductal carcinoma was diagnosed in all cases. The grades classification was as follow: grade 2 (30%) and grade 3 (70%). 70% of cases had lymph node metastasis. Estrogen and progesterone receptors (ER,PR) were positive in 60% of tumors. Overexpression of HER2 was positive (Score3) in one case. Luminal B was the most common subtype in our study. Conclusion: Male breast cancer is a rare disease with a poor prognosis despite the recent increase in incidence in recent years. The diagnosis is often delayed and injuries are treated in advanced stages.